Biocatalytic and chemical derivatization of the fungal meroditerpenoid chevalone E. Issue 7 (18th February 2022) - Xiao, Zong-Hua; Dong, Jia-Yu; Li, Ao; Dai, Jia-Meng; Li, Yan-Ping; Hu, Qiu-Fen; Shao, Li-Dong; Matsuda, Yudai; Wang, Wei-Guang
Abstract : The structural derivatization of the fungal meroditerpenoid chevalone E was achieved by biocatalytic and chemical approaches. Some of the new chevalone analogues, in combination with doxorubicin, synergistically inhibit the growth of breast cancer cells. Abstract : Fungal meroditerpenoids include diverse molecules with structural complexity and a broad range of biological activities. We have previously obtained the meroditerpenoid chevalone E (1 ) and its oxidized analogues by heterologously expressing a cryptic gene cluster found in the fungus Aspergillus versicolor . In this study, we further derivatized 1 into eight chevalone analogues using a single dehydrogenase involved in another meroterpenoid pathway. Some of the new analogues harbor the characteristic hemiacetal bridge, which can be transformed into the spirolactone moiety by simple chemical synthesis. Furthermore, some of the new chevalone analogues exhibit the synergetic inhibition of MDA-MB-231 breast cancer cell viability when combined with the chemotherapeutic agent doxorubicin.